Sadness might isolate you in a non-smelling world: olfactory perception and depression - Schablitzky, Sylvia; Pause, Bettina M. (Frontiers in Psychology, 2014)
Major depressive disorder (MDD) occurs with a high prevalence among the mental illnesses. MDD patients experience sadness and hopelessness, with blunted affective reactivity. However, such depressive episodes are also key symptoms in other depressive disorders, like Bipolar Disorder (BPD) or Seasonal Affective Disorder (SAD). Moreover, depressive symptoms can also be found in healthy individuals, but are experienced as less severe or for a shorter duration than in patients. Here, it is aimed to summarize studies investigating odor perception in depression, including depressive states in healthy individuals and patient populations. Odor perception in depression has been assessed with psychophysical methods (olfactory sensitivity, odor identification and discrimination), and odor ratings (intensity, emotional valence, familiarity). In addition, some studies investigated affective reactions to odors, and physiological and anatomical correlates of odor perception in depression. The summary reveals that MDD is associated with a reduced olfactory sensitivity. However, odor identification and discrimination scores seem to be unaffected by depression. The reduced olfactory sensitivity might be associated with a reduced ability to encode olfactory information and a reduced volume of the olfactory bulb. While similar processes seem to occur in healthy individuals experiencing depressive states, they cannot be observed in BPD or SAD patients. However, in order to conclude that the reduced olfactory sensitivity is directly linked to depression, it is suggested that studies should implement control measures of cognitive performances or perceptual abilities in other stimulus modalities. It is concluded that the reduced olfactory performance in MDD patients seems to be disorder-, modality-, and test-specific, and that the application of an appropriate olfactory and cognitive test-battery might be highly useful in the differential diagnosis of MDD.